2016
DOI: 10.1016/j.marpolbul.2016.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Sources and sinks of microplastics in Canadian Lake Ontario nearshore, tributary and beach sediments

Abstract: Microplastics contamination of Lake Ontario sediments is investigated with the aim of identifying distribution patterns and hotspots in nearshore, tributary and beach depositional environments. Microplastics are concentrated in nearshore sediments in the vicinity of urban and industrial regions. In Humber Bay and Toronto Harbour microplastic concentrations were consistently >500 particles per kg dry sediment. Maximum concentrations of ~28,000 particles per kg dry sediment were determined in Etobicoke Creek. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
256
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 569 publications
(277 citation statements)
references
References 57 publications
17
256
2
2
Order By: Relevance
“…According to this model, most of the floating plastics sampled in the western and central basin would have been in Lake Erie for <2 years. However, while most virgin plastic used in consumer products-especially one-time use plastic (PlasticsEurope: Association of Plastics Manufacturers, 2015)-is predicted to be positively buoyant, plastic litter is readily found in sediment (Corcoran et al, 2015;Ballent et al, 2016). This can be attributed to denser polymer types sinking, but there are other dynamic changes in the buoyant density that plastics are likely to undergo once in the environment, e.g., oxidation or biofouling.…”
Section: Plastic Density Drastically Impacts Residence Time In the Lakementioning
confidence: 99%
See 1 more Smart Citation
“…According to this model, most of the floating plastics sampled in the western and central basin would have been in Lake Erie for <2 years. However, while most virgin plastic used in consumer products-especially one-time use plastic (PlasticsEurope: Association of Plastics Manufacturers, 2015)-is predicted to be positively buoyant, plastic litter is readily found in sediment (Corcoran et al, 2015;Ballent et al, 2016). This can be attributed to denser polymer types sinking, but there are other dynamic changes in the buoyant density that plastics are likely to undergo once in the environment, e.g., oxidation or biofouling.…”
Section: Plastic Density Drastically Impacts Residence Time In the Lakementioning
confidence: 99%
“…Field surveys have confirmed the presence of microplastics in Great Lakes surface water (Eriksen et al, 2013;Mason et al, 2016), sediment (Corcoran et al, 2015;Ballent et al, 2016), and beaches (Zbyszewski and Corcoran, 2011;Hoellein et al, 2014;Zbyszewski et al, 2014;Driedger et al, 2015), as well as the rivers (Baldwin et al, 2016) and wastewater treatment plant (WWTP) effluents (Michielssen et al, 2016) that directly feed into the Great Lakes. Yet, these data are sparse.…”
Section: Introductionmentioning
confidence: 96%
“…In America, most research has concentrated in Canada and the USA, ( Fig. 2; Online Resource 1), particularly in the Great Lakes area [6,18,26,80,96,97], including the St. Lawrence River watershed [12]. Of these, only two studies collected data from freshwater bottom sediments [12,18], and one considered open-water loading (the Laurentian Great Lakes system) [26].…”
Section: Microplastics In Freshwater Environmentsmentioning
confidence: 99%
“…black or dark blue, light blue, and red). Micro-fibres of similar characteristics 337 were observed in other freshwater ecosystems (Ballent et al, 2016), where fibres <2 mm identified 338 visually with a stereo microscope were found to be the predominant type of MPs, alongside fragments 339 in the same size range. In the River Kelvin sediment, fibres were observed in isolation, in clusters and 340 embedded in sediment grains (Fig.…”
Section: Microfibres 334 335mentioning
confidence: 58%
“…5). Similarly, others have reported the predominance of fibres (Ballent et al, 2016;Su et al, 2016), 358 especially in systems associated with wastewater treatment as such fibres typically break off synthetic 359 textiles and are released via household sewage (Browne et al, 2011;Magnusson and Nóren, 2014).treatment facility, it has been suggested that fibres can be transported for greater distances (Ballent et 362 al., 2016), thus their presence may be attributed to distant inputs upstream from the study site. 363…”
mentioning
confidence: 95%